Design of Servo-Controlled Titrant Flux Regulation System - Zulma, Degito; Sari, Mona Berlian; Yohandri, Yohandri; Darvina, Yenni (Department of Physics, Universitas Negeri Padang, 2024)
The advancement of automation in laboratory instrumentation has significantly transformed the field of chemical analysis by enhancing precision, efficiency, and reproducibility. The development of an advanced titrant flux regulation system presents substantial potential benefits. This research focuses on the design of a Titrant Flux Regulation System utilizing a Servo Motor and PCA9685 Driver for Automated Titrators, with the aim of improving the accuracy of titration processes. The system employs a servo control mechanism driven by the PCA9685 driver to precisely maneuver the burette crank. The methodology encompasses system design, simulation, prototyping, and performance testing. A microcontroller-controlled servo motor ensures precise movements of the burette crank, enabling accurate titrant delivery. The developed prototype demonstrates the ability to regulate titrant flow with high precision, facilitating fine-tuned control of titrant volume to meet specific titration requirements. The servo and PCA9685-based system shows significant promise for application in automated titrators, offering enhanced accuracy and control of titrant flow, thereby optimizing the titration process.